Ungestört bei der Sache? Eine Befragung von Lehrkräften an Grund- und Förderschulen zur Sachunterrichtspraxis unter Bedingungen des Förderschwerpunktes emotionale und soziale Entwicklung - Schroeder, René (Perspektiven sonderpädagogischer Forschung, 2022)
The assumption social studies and science in primary education to be a key-component in realizing inclusive teaching in primary classrooms for all children but especially for children with emotional and behavioral difficulties in special needs education is fundamental to this work. Nevertheless, there is nearly no research-based evidence on how potentials for inclusion and social learning are used in primary schools or special schools nor is there research on how teaching is planned, realized, and accounted for. This desiderate is addressed in this work. By analyzing and thereby linking the discourses in social studies and science in primary education and special education for children with emotional and behavioral difficulties, principles for education and teaching in both domains are summarized. This is the theoretical foundation of a mixed- methods-study with a two-step-design to explore the teaching practices and teachers' beliefs of teachers in inclusive primary schools and special schools for children with emotional and behavioral difficulties in North Rhine-Westfalia, Germany. The study is composed of a partly standardized questionnaire survey (n= 80) followed by qualitive interviews with teachers as experts (n = 10). Data is consequently triangulated to explore the structure of teaching practices and possible determinants concerning the teachers, framework conditions and the learning groups. The results indicate that life-world-oriented education, disturbed student-teacher-interactions and professional lesson planning between child, method and teaching materials are important issues for the development of inclusive teaching in social studies and science in primary education. Consequently, the study outlines future fields of research and development derived from an explorative view at teaching practices in inclusive and separative education settings.